HUBUNGAN KAUSALITAS ANTARA INVESTASI DAN PRODUK DOMESTIK REGIONAL BRUTO DI WILAYAH SUMATERA DENGAN MODEL PANEL VECTOR AUTO REGRESSION (PVAR) - Andre Riswanto (Yayasan Education and Social Center, 2023)
Gross Regional Domestic Product (GRDP) records the total value of goods and services produced by a provincial/ district/ city economy for one year Ever. This research aims to analyze and determine the causality relationship and direction between Domestic Investment (DI), Foreign Investment (FI), and Gross Regional Domestic Product (GRDP) in Sumatra Region. The research approach of this study is quantitative. The data sources used in this study are the secondary sources obtained from the Indonesian Central Agency (BPS). Data analysis using panel vector autoregression method (PVAR). The results showed no two-way causality relationship and one-way between Domestic Investment (DI) and Foreign Direct Investment (FDI). A one-way causality relationship exists between Domestic Investment (DI) and Gross Regional Domestic Product (GRDP) in Sumatra Region. There is no causality relationship between two-way and one-way causality between Foreign Investment (FI) and Gross Regional Domestic Product (GRDP) in Sumatra Region